2012
DOI: 10.1021/la301783q
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Adhesion of Gecko-Inspired PDMS Flaps on Rough Surfaces

Abstract: Geckos have developed a unique hierarchical structure to maintain climbing ability on surfaces with different roughness, one of the extremely important parameters that affect the friction and adhesion forces between two surfaces. Although much attention has been paid on fabricating various structures that mimic the hierarchical structure of a gecko foot, yet no systematic effort, in experiment or theory, has been made to quantify the effect of surface roughness on the performance of the fabricated structures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 53 publications
2
73
0
Order By: Relevance
“…First, the rough surfaces exhibit the highest friction forces and stick-slip magnitude. This can be explained through an interlocking mechanism [33] (figure 6) where the roughness of the surface matches with the interspacing of the array of flaps. Based on the values in table 1, the average distance between asperities on the rough surface (6.7 + 3.5 mm) shows that it is possible to fit the flap dimensions (10 mm  3.5 mm) in between some spots where the asperities are more spread out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the rough surfaces exhibit the highest friction forces and stick-slip magnitude. This can be explained through an interlocking mechanism [33] (figure 6) where the roughness of the surface matches with the interspacing of the array of flaps. Based on the values in table 1, the average distance between asperities on the rough surface (6.7 + 3.5 mm) shows that it is possible to fit the flap dimensions (10 mm  3.5 mm) in between some spots where the asperities are more spread out.…”
Section: Discussionmentioning
confidence: 99%
“…properties of a gecko footpad were fabricated and have been described elsewhere [16,33]. A modified SFA (SurForce LLC) [16,43] was used to measure the normal F ?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the tribological properties of conventional bulk plastics [35][36][37][38], rubber-like materials [39], fiber-reinforced composites [40], polymer nanocomposites [41][42][43], cross-linked hydrogels [44], end-grafted polymers (a.k.a. polymer brushes) [45], mammalian articular joints [46], gecko-inspired surfaces [47], and mussel-inspired coatings [48] have been investigated. For viscoelastic solids, such as polymers, it has been shown that friction is velocity-dependent and Equation (1) cannot be valid over a wide range of sliding velocities.…”
Section: Friction Laws For Viscoelastic Solidsmentioning
confidence: 99%
“…Their model predicts the peeling behavior of adhesive tapes from a glass substrate at peel angles at 90°or less without considering substrate roughness. Pesika's PZ model adds an angle-dependent multiplier to the Kendall equation [8]. A more widely applicable PZ model including large deformation and pre-strain of the backing layer was presented by Molinari and Ravichandran [5].…”
Section: Introductionmentioning
confidence: 99%